2014
DOI: 10.1186/1550-2783-11-6
|View full text |Cite
|
Sign up to set email alerts
|

Effects of short-term ingestion of Russian Tarragon prior to creatine monohydrate supplementation on whole body and muscle creatine retention and anaerobic sprint capacity: a preliminary investigation

Abstract: BackgroundExtracts of Russian Tarragon (RT) have been reported to produce anti-hyperglycemic effects and influence plasma creatine (Cr) levels while supplementing with creatine monohydrate (CrM). The purpose of this preliminary study was to determine if short-term, low-dose aqueous RT extract ingestion prior to CrM supplementation influences whole body Cr retention, muscle Cr or measures of anaerobic sprint performance.MethodsIn a double-blind, randomized, and crossover manner; 10 recreationally trained males … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 25 publications
0
4
1
2
Order By: Relevance
“…These findings replicate results from a previous study where leg stiffness (both absolute and relative) was compromised ( p < 0.001) after a soccer specific fatigue protocol ( Lehnert et al, 2016 ). Our results can be also compared with those of another recent study ( Oliver et al, 2014 ) in which muscle stiffness was determined in 15-year-old soccer players. The authors reported a non-significant decrease in terms of absolute muscle stiffness after a fatigue protocol, but this might be attributed to the fact that they used a soccer-specific intermittent exercise test performed on a non-motorised treadmill and the duration of the test only corresponded to one half of simulated match play.…”
Section: Discussionmentioning
confidence: 61%
“…These findings replicate results from a previous study where leg stiffness (both absolute and relative) was compromised ( p < 0.001) after a soccer specific fatigue protocol ( Lehnert et al, 2016 ). Our results can be also compared with those of another recent study ( Oliver et al, 2014 ) in which muscle stiffness was determined in 15-year-old soccer players. The authors reported a non-significant decrease in terms of absolute muscle stiffness after a fatigue protocol, but this might be attributed to the fact that they used a soccer-specific intermittent exercise test performed on a non-motorised treadmill and the duration of the test only corresponded to one half of simulated match play.…”
Section: Discussionmentioning
confidence: 61%
“…The authors suggest that theoretically, ingesting RT extract prior to Cr loading may enhance insulin sensitivity and thereby promote greater Cr absorption/retention. In a follow-up study by this group, Oliver et al [ 69 ] used a double-blind, randomized, and crossover manner to examine the effect of consuming RT during 5 days of CrM loading. Recreationally trained males ingested 500 mg of aqueous RT extract or 500 mg placebo 30 min prior to ingesting 5 g of CrM twice per day for 5 days and then repeated after a 6-week washout period.…”
Section: Creatine With Insulin Mimickersmentioning
confidence: 98%
“…Se ha demostrado que el monohidrato de creatina (MC): -Incrementa los niveles de fosfocreatina en el músculo, molécula esencial de la vía anaeróbica aláctica para la resíntesis del ATP (trifosfato de adenosina) (3,4,7,8). -Facilita la hipertrofia muscular (9).…”
Section: Mecanismo De Acciónunclassified